The combination of plyometric and ladder drills can improve acceleration and footwork skills in badminton players - Muhammad Labib Siena Ar Rasyid; Oce Wiriawan; Afif Rusdiawan; Laily Mita Andriana; Enarnimas Dwi Ratna Damayanti (Physical Education and Sports: Studies and Research, 2026)
Background: Recognized globally as the fastest racket sport in the world, badminton demands exceptional acceleration and footwork skills for competitive success. However, many intermediate players often struggle to produce the explosive power needed for fast-paced rallies. To enhance these physical attributes, targeted training interventions, such as a hybrid regimen of plyometric and ladder drills, are often required. Objectives: This study aims to analyze the efficacy of integrating plyometric exercises with ladder drills in enhancing acceleration and footwork proficiency among badminton players. Methods: This research employed a quasi-experimental design with a non-equivalent control group. Through purposive sampling, 24 male participants (aged 14-16 years) with at least 2 years of training experience, good health, and no history of recent injuries were selected. They were assigned to either the PLD Group (age: 15.00 ± 0.74 years; height: 162.00 ± 0.07 cm; weight: 50.58 ± 5.68 kg; BMI: 19.20 ± 0.88 kg/m²) or the CV Group (age: 15.00 ± 0.85 years; height: 162.08 ± 0.08 cm; weight: 51.75 ± 8.05 kg; BMI: 19.59 ± 1.56 kg/m²). The intervention spanned six weeks, with three sessions per week. Performance in acceleration was assessed using a 10-meter sprint, and footwork skills were assessed using the footwork skills test (Tohar version) pre- and post-intervention. Data analysis employed the Wilcoxon signed-rank and the Mann-Whitney tests. Results: The Wilcoxon analysis indicated that both the PLD and CV Groups achieved improvements in acceleration and footwork skills (p<0.05). However, the Mann-Whitney test revealed a statistically significant difference between the two groups, with the PLD Group demonstrating superior gains in both acceleration (p<0.05) and footwork skills (p<0.05) compared to the CV Group. Conclusions: Integrating plyometric training and ladder drills is an effective strategy for significantly improving acceleration and footwork skills in badminton players.